A FRAMEWORK FOR EDGE COMPUTING TO SECURE IOT DEVICES - Chowdhury, S M Abrar Kabir (Universiti Malaysia Sarawak (UNIMAS), 2020)
nternet of Things (IoT) is a big role player in the Industrial revolution 4.0 by having vast pawer of information transmission. Easy mobility, the capability of internet connection, smart and dynamic functioning and user-friendly behaviour gives IoT to get the big market of the user within a very short time. Edge computing is a distributed, open IT architecture that features decentralized processing power, enabling mobile computing and Internet of Things (IoT) technologies. In edge computing, data is processed by the device itself or by a local computer or server, rather than being transmitted to a data centre. Secure data handling in edge computing in IoT high emergence because IoT has low resource availability both in hardware and software which causes the big risk of data manipulation. Sometimes it can be a life risk situation by hacking. My attempt here is to make a conceptual framework for IoT edge computing.